Philosophy with Children How does the practice of philosophy nurture a young child's natural ability to think philosophically and encourage him/her to participate in a democratic community of enquiry? - Arigho, Louise (My University, 2017)
Philosophy enables us to be critical, independent thinkers particularly in a fast-paced digital world. Philosophy with Children is a pedagogy whereby the voice of the child is upheld, their agency is enabled and their critical thinking is developed. The importance of Philosophy with Children is especially relevant to the current Irish Primary School Curriculum which is content heavy and where a strong emphasis is placed upon mathematical and linguistic knowledge. The dialogic nature of philosophy encounters encourages the exploration of children's thoughts and wonderings, which provokes continued curiosity and fosters intrinsic learner motivation. The beauty of Philosophy with Children is that there are no wrong answers. It is always open and interpretive in nature, giving the young child a sense of power and ownership of his/her learning. This study utilises an action research approach to critically examine the nature of children's philosophical responses through everyday topics. It assesses the nature of their responses in terms of language, participation and confidence levels. Furthermore, it also explores the role of the classroom teacher as a facilitator of these encounters. The sessions were integrated into the weekly curriculum which provides an opportunity for this in Learn Together and Oral Language. The results of the study show that children in the early years context are more than capable of entering into a dialogue in a community of enquiry, and that they display a range of higher-order thinking skills when doing so. Philosophy with Children is a suitable means to begin to foster the development of a critical citizenry through engagement with democratic practices in the early years context. In addition, the educator can play an influential role in creating a classroom environment conducive to dialogue.
Master in Education Studies (Early Childhood Education)
Keywords: Research Subject Categories; Philosophy; Independent thinking; Pedagogy; Critical thinking; Irish Primary School Curriculum